IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN YOUTUBE TERHADAP HASIL BELAJAR PPKN SISWA DI KELAS IV SD NEGERI 101927 SEKIP KECAMATAN LUBUK PAKAM - Rahman, Aulia (Jurnal Tematik, 2022)
The 21st century is an era of digitalization that affects the character of children in their development and growth. The teacher is still monotonous and has not been innovative in using learning media, the teacher has not used videos that present problems according to the learning material, so students tend to be passive and less interested in participating in learning so that it affects the learning outcomes of Civics for fourth grade students at SD Negeri 101927 Sekip, Lubuk Pakam District . In delivering the material on the rights and obligations of food to fourth grade students, videos are needed that are in accordance with the material so that students are more active, interested and able to understand and improve student learning outcomes. The media used in the material is a video regarding the rights and obligations of appropriate plants. This is done in accordance with constructivist learning theory, which is to build interest and understanding of students to be more active in participating in learning. Students are more interested if the media is presented in audio-visual form such as videos from YouTube that are in accordance with the learning material. In several previous studies it was stated that the use of Information Technology-based media is one step that can increase student interest and learning outcomes. Therefore, teachers are expected to use YouTube-assisted learning media in order to increase interest and learning outcomes for fourth grade Civics at SD Negeri 101927 Sekip, Lubuk Pakam District.